Hubungan Suntik KB 3 Bulan Terhadap Kelancaran Menyusui Di BPM Perawati Desa Karya Teladan Kabupaten Musi Rawas Sumatera Selatan - Resmi, Ermi; Sulastri, Mepi; Umami, Desi Aulia (Jurnal Kesehatan Mitra Sekawan, 2024)
The use of family planning according to the type of family planning tool or method in Indonesia is dominated by the use of injectable family planning. The problem of breastfeeding infertility is a common side effect of using 3-month injectable family planning. The results of a survey of 3-month injectable family planning acceptors who visited BPM Perawati mostly (80%) experienced breastfeeding instability. The purpose of the study was to determine the relationship between 3-month injections and breastfeeding fluency at Bpm Perawati Karya Teladan Village, Musi Rawas Regency, South Sumatra. Analytical survey research design cross sectional approach. The population in this study was 132 acceptors of 3-month injections. The sample in this study was 57 3-month injectable acceptors who were taken by purposive sampling by selecting the number of samples and populations according to the inclusion and exclusion criteria. The results of the study obtained more than half (60%) of the use of 3-month injectable birth control > 1 year and more than half (68%) who experienced unsmooth breastfeeding. The results of the chi-square test analysis p value = 0.010 < α = 0.05 concluded that there was a relationship between 3-month injectable Kb and smooth breastfeeding at Bpm Perawati Karya Teladan Village, Musi Rawas Regency, South Sumatra. Suggestions for health workers to be able to provide support and improve services to KB acceptors injecting 3 months.